Freshening effect on the osmotic response of the Antarctic spiny plunderfish Harpagifer antarcticus. Issue 6 (11th February 2021) - Vargas‐Chacoff, Luis; Dann, Francisco; Paschke, Kurt; Oyarzún‐Salazar, Ricardo; Nualart, Daniela; Martínez, Danixa; Wilson, Jonathan M.; Guerreiro, Pedro M.; Navarro, Jorge M.
Abstract: Global warming is having a significant impact around the world, modifying environmental conditions in many areas, including in zones that have been thermally stable for thousands of years, such as Antarctica. Stenothermal sedentary intertidal fish species may suffer due to warming, notably if this causes water freshening from increased freshwater inputs. Acute decreases in salinity, from 33 down to 5, were used to assess osmotic responses to environmental salinity fluctuations in Antarctic spiny plunderfish Harpagifer antarcticus, in particular to evaluate if H. antarcticus is able to cope with freshening and to describe osmoregulatory responses at different levels (haematological variables, muscle water content, gene expression, NKA activity). H. antarcticus were acclimated to a range of salinities (33 as control, 20, 15, 10 and 5) for 1 week. At 5, plasma osmolality and calcium concentration were both at their lowest, while plasma cortisol and percentage muscle water content were at their highest. At the same salinity, gill and intestine Na + ‐K + ‐ATPase (NKA) activities were at their lowest and highest, respectively. In kidney, NKA activity was highest at intermediate salinities (15 and 10). The salinity‐dependent NKA mRNA expression patterns differed depending on the tissue. Marked changes were also observed in the expression of genes coding membrane proteins associated with ion and water transport, such as NKCC2, CFTR and AQP8, and in the expression of mRNA for the regulatory hormone prolactin (PRL) and its receptor (PRLr). Our results demonstrate that freshening causes osmotic imbalances in H. antarcticus, apparently due to reduced capacity of both transport and regulatory mechanisms of key organs to maintain homeostasis. This has implications for fish species that have evolved in stable environmental conditions in the Antarctic, now threatened by climate change.